2023
DOI: 10.3390/diagnostics13071292
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Brain Network Structure between Patients with High and Low Generalized Anxiety Disorder

Abstract: To investigate the differences in functional brain network structures between patients with a high level of generalized anxiety disorder (HGAD) and those with a low level of generalized anxiety disorder (LGAD), a resting-state electroencephalogram (EEG) was recorded in 30 LGAD patients and 21 HGAD patients. Functional connectivity between all pairs of brain regions was determined by the Phase Lag Index (PLI) to construct a functional brain network. Then, the characteristic path length, clustering coefficient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…It has been suggested that individuals with DD sacrifice connections between the frontal and parietal regions to achieve long-distance connections [ 45 ]. Additionally, the brain functional reorganization in GAD patients involves alterations in both the number [ 21 ] and the strength of connections [ 13 ]. The abnormal activation in the high-frequency beta band is indicative of anxiety manifestations in both DD and GAD [ 11 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that individuals with DD sacrifice connections between the frontal and parietal regions to achieve long-distance connections [ 45 ]. Additionally, the brain functional reorganization in GAD patients involves alterations in both the number [ 21 ] and the strength of connections [ 13 ]. The abnormal activation in the high-frequency beta band is indicative of anxiety manifestations in both DD and GAD [ 11 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In EEG signals, there are often numerous artifacts. In previous studies [ 11 , 12 , 13 ], we utilized an independent component analysis (ICA) combined with manual artifact removal to achieve satisfactory results. Additionally, traditional methods of EEG analysis involve linear analysis [ 14 ], nonlinear analysis [ 15 ], and brain functional connectivity analysis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the application of EEG to GAD has been continuously explored to help uncover the complex neuro-electrophysiological mechanism and provide more effective detection methods. Previous studies have utilized EEG to observe changes in the brain of GAD patients, such as increased brain activity ( 18 ) and alterations in brain network structure ( 19 ). Furthermore, by extracting various types of EEG features, such as functional connectivity ( 19 ), power spectral density ( 20 ), and correlation dimension ( 21 ), researchers found significant differences in features between GAD patients and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have utilized EEG to observe changes in the brain of GAD patients, such as increased brain activity ( 18 ) and alterations in brain network structure ( 19 ). Furthermore, by extracting various types of EEG features, such as functional connectivity ( 19 ), power spectral density ( 20 ), and correlation dimension ( 21 ), researchers found significant differences in features between GAD patients and healthy controls. Until now, EEG has been widely used to assist in the diagnosis of various psychiatric disorders, such as anxiety ( 22 , 23 ), depression ( 24 , 25 ), obsessive-compulsive disorder ( 26 , 27 ), Alzheimer’s ( 28 , 29 ), schizophrenia ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%